An assessment of needs and expectations before the construction of an interactive space for communication, information and history-educational learning - Mengual-Andrés, Santiago; Payá Rico, Andrés; Roig Vila, Rosabel (Revista Complutense de Educación, 2015)
Awareness of the huge possibilities that Web 2.0 offers to pedagogy, participation and scientific collaboration led the authors of the present paper to consider the detection of needs and expectations regarding  the creation of a virtual platform defined by an interactive space or social network for history of education and history-educational heritage. Thanks to an assessment, made possible through a survey carried out among a group of teaching experts and history of education researchers,  we were allowed to reach a number of relevant conclusions about specific aspects (knowledge and use, expectations, components, etc.) that will guide our ad hoc construction of the aforesaid platform. It is worth highlighting the poor knowledge and limited use of both generic and specific social networks, as well as of other web applications, in addition to which it deserves to be stressed that the age of participants did not determine the perception of importance assigned to ICTs when it comes to development within teaching and research.
Keywords: web 2.0 technologies; social networks; collaboration; history of education; heritage education